The effect of ordinal rank at school on students’ academic performance - Marcenaro-Gutiérrez, Óscar David; Prieto-Latorre, Claudia; López-Agudo, Luis Alejandro (XLVI REUNIÓN DE ESTUDIOS REGIONALES, 2021)
School peers can condition students’ academic performance in different ways. On the one hand, students’ academic progression is driven by the level of academic performance of their peers. Second, students’ self-perception about their own ability is made of their comparison with their peers. This research investigate these two effects of having high-skilled peers, that seems to run in opposite directions. Additionally, in this study we analyse the effect of students’ relative rank within their school in terms of their socioeconomic and cultural status. We follow an empirical approach using data from Canary Island, which is a Spanish region which exhibits a low level of academic performance. The estimation procedure used has been a value added model, which account for previous academic performance in absolute terms and also control for students’ socioeconomic level. Results show that having high-skilled peers in 3rd grade of primary is negative for students’ educational attainment in 6th grade. We have also explored the existence of different behaviour by gender. Result are consistent across gender, although it seems that being on the top of their class has slightly higher influence on girls’ than boys’ academic performance. This result has consequence on parental decisions about school choice, and reveals that having high-skilled classmates has drawbacks for students’ self-concept of their academic skills.
Keywords: Educación primaria; Rendimiento académico; Primary education; Relative position; Academic performance; Value added model